Factors contributing to partial remission in type 1 diabetes: analysis based on the insulin dose‐adjusted HbA1c in 3657 children and adolescents from Germany and Austria. Issue 6 (15th July 2016) - Nagl, Katrin; Hermann, Julia M.; Plamper, Michaela; Schröder, Carmen; Dost, Axel; Kordonouri, Olga; Rami‐Merhar, Birgit; Holl, Reinhard W.
Abstract : Objective: Insulin dose‐adjusted hemoglobin A1c (HbA1C, IDAA1c) correlates well with stimulated C‐peptide levels, but has not yet been evaluated in a large cohort of patients with Type 1 diabetes (T1D). Methods: We investigated prevalence of partial remission (PREM) defined by IDAA1c ≤9 in 3657 in children with new‐onset T1D who were continuously followed over 6 years. We evaluated the predictors of PREM using the multicenter database from the DPV (Diabetes Patienten Verlaufsdokumentation) registry. Results: PREM occurred in 71% of patients. Median duration was 9 (0‐21) months. Compared to children <5 years at T1D onset, those aged 5‐10 and ≥10 years had twice the chance of developing PREM (OR: 2.08, CI: 1.67‐2.60; P < .001 and OR: 2.16, CI: 1.70‐2.75; P < .001). Boys were more likely to develop PREM than girls (OR 1.41, CI: 1.18‐1.69; P = .0002). Further predictors for PREM were: ketoacidosis, autoantibodies, and HbA1c at T1D onset. These results were confirmed by quantile regression analysis with duration of PREM as dependent variable. Conclusion: This research on a large cohort provides insight into epidemiologic characteristics of PREM in T1D defined by IDAA1c. As IDAA1c does not discriminate between insulin sensitivity and secretion, available data cannot resolve whether the sex‐difference in PREM reflects innate higher insulin resistance in girls, or better beta‐cell recovery in boys. Further research is needed to clarify the usefulness and performance of IDAA1c in clinical practice.